2016
DOI: 10.1152/ajpcell.00185.2015
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of the Sec7 domain Arf guanine nucleotide exchange factor GBF1 is dispensable for Golgi localization and function but regulates degradation

Abstract: Members of the large Sec7 domain-containing Arf guanine nucleotide exchange factor (GEF) family have been shown to dimerize through their NH2-terminal dimerization and cyclophilin binding (DCB) and homology upstream of Sec7 (HUS) domains. However, the importance of dimerization in GEF localization and function has not been assessed. We generated a GBF1 mutant (91/130) in which two residues required for oligomerization (K91 and E130 within the DCB domain) were replaced with A and assessed the effects of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 63 publications
14
20
0
Order By: Relevance
“…We ensured that the loss of membrane association of GBF1/795/ LF was not due to misfolding by showing analogous migration patterns of GBF1/795/LF, GBF1/795 and GBF1/795/KF, similar to that previously reported for endogenous GBF1 (Bhatt et al, 2016) on blue native gel electrophoresis ( Fig. 2E).…”
Section: Results and Discussion Gbf1 Recruitment To Golgi Membranes Rsupporting
confidence: 76%
“…We ensured that the loss of membrane association of GBF1/795/ LF was not due to misfolding by showing analogous migration patterns of GBF1/795/LF, GBF1/795 and GBF1/795/KF, similar to that previously reported for endogenous GBF1 (Bhatt et al, 2016) on blue native gel electrophoresis ( Fig. 2E).…”
Section: Results and Discussion Gbf1 Recruitment To Golgi Membranes Rsupporting
confidence: 76%
“…The FRAP behavior of wild-type GBF1 when expressed alone in cells is shown in Figure 3A, and is consistent with previously published values. As shown in Table 1, the t1/2 of 7.5 sec in this study is similar to the t1/2 of 9.4 sec reported previously in Bhatt et al, 2016, but lower than the previously reported values of t1/2 of 17 sec (Szul et al, 2005) and 30 sec (Niu et al, 2005). It is likely that the faster FRAP of the more recent studies is due to faster acquisition rates of now available imaging systems.…”
Section: Kinetic Behavior Of Gbf1 Is Diffusion-limitedsupporting
confidence: 84%
“…For the semi-log method, we decided to use the former strategy. From past reports monitoring the recovery of COPI coat components over two or three minutes, it was observed that not much additional recovery occurs after 60 seconds, so there is little information to be gathered in the latter portion of the recovery curve (Bhatt et al, 2016;Niu et al, 2005;Szul et al, 2005). The first 30-40 seconds seem to be the richest in information.…”
Section: Theoretical Correlation Between Frap and Reaction-diffusion mentioning
confidence: 99%
“…In addition, GBF1 contains five non-catalytic domains: the N-terminal dimerization and cyclophilin binding (DCB), the homology upstream of Sec7 (HUS), and three C-terminal downstream of Sec7 (HDS1-3) domains (33, 36). The functions of these non-catalytic domains are not well understood, but the N-terminal DCB and HUS domains have been implicated in inter- and intra-molecular interactions important for GBF1 dimerization and its association to membranes (43, 44), while the HDS1-3 domains have been suggested to facilitate GBF1 association with membranes (Bouvet et al, 2013; Chen et al, 2016; Ellong et al, 2011; Meissner et al, 2018 and unpublished results).…”
Section: Introductionmentioning
confidence: 99%